2020
DOI: 10.1038/s41398-020-0804-z
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the genetic bases of OCD dimensions: a pilot genome-wide association study

Abstract: The multidimensional nature of obsessive-compulsive disorder (OCD) has been consistently reported. Clinical and biological characteristics have been associated with OCD dimensions in different ways. Studies suggest the existence of specific genetic bases for the different OCD dimensions. In this study, we analyze the genomic markers, genes, gene ontology and biological pathways associated with the presence of aggressive/checking, symmetry/order, contamination/cleaning, hoarding, and sexual/religious symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…A general PRS for OCD lumps all of these hypothetical dimension‐specific SNPs together, so that a lack of an association is not surprising. A recent GWAS of obsessive‐compulsive symptom dimensions also supports the notion that divergent genes and pathways may be involved in the expression of different symptom dimensions, although no genome‐wide significant SNPs have been found, so far (71).…”
Section: Discussionmentioning
confidence: 86%
“…A general PRS for OCD lumps all of these hypothetical dimension‐specific SNPs together, so that a lack of an association is not surprising. A recent GWAS of obsessive‐compulsive symptom dimensions also supports the notion that divergent genes and pathways may be involved in the expression of different symptom dimensions, although no genome‐wide significant SNPs have been found, so far (71).…”
Section: Discussionmentioning
confidence: 86%
“…Focusing on compulsive symptoms only also increased the ability to identify genome-wide significant genes. Recently, a smaller study of 399 patients with OCD using a gene-based analysis has reported that SETD3 was associated with hoarding symptoms only ( p = 1.89 × 10 −8 ) and that biological pathways and processes were differentially associated across symptom dimensions (Alemany-Navarro et al, 2020 ).…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Approaches to identify genes associated with OCD typically take advantage of these frameworks and often attempt to either narrow the phenotypic definition to reduce heterogeneity or broaden the phenotypic definition to leverage observed genetic or clinical relationships between OCD and other traits. Methodologies aimed at narrowing the phenotypic definition may use a strict case definition or only include cases with clinically diagnosed OCD [ 1 , 17 , 18 ], childhood-onset OCD [ 4 , 7 ], OCD from multiplex families [ 19 , 20 ], OCD with tics [ 21 ], severe OCD, or specific OC symptoms [ 22 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only two GWAS studies to date have examined the unique and shared genetic architecture of OC symptom factors, one of which used data from clinical OCD patients [ 22 ], and the other of which used data collected in the general population [ 25 ]. These studies, while suggesting some genetic sharing between symptom subtypes, still require replication.…”
Section: Introductionmentioning
confidence: 99%